Determinants of city growth in Brazil - Daniel da Mata; Uwe Deichmann; J. Vernon Henderson; Somik V. Lall; Hyoung Gun Wang (Institute for Applied Economic Research (ipea), 2015)
In this paper, we examine the determinants of Brazilian city growth between 1970 and 2000. We consider a model of a city, which combines aspects of standard urban economics and the new economic geography literatures. For the empirical analysis, we constructed a dataset of 123 Brazilian agglomerations, and estimate aspects of the demand and supply side as well as a reduced form specification that describes city sizes and their growth. Our main findings are that increases in rural population supply, improvements in inter-regional transport connectivity and education attainment of the labor force have strong impacts on city growth. We also find that local crime and violence, measured by homicide rates impinge on growth. In contrast, a higher share of private sector industrial capital in the local economy stimulates growth. Using the residuals from the growth estimation, we also find that cities who better administer local land use and zoning laws have higher growth. Finally, our policy simulations show that diverting transport investments from large cities towards secondary cities do not provide significant gains in terms of national urban performance.
Keywords: R11; O1; O47; 330